The Application of Restorative Justice in Domestic and Child Violence Cases in Indonesia and Finland - Fatin Hamamah; Didi Sukardi; Shirin Kulkarni (SASI)
Introduction: Restorative justice (RJ) is an alternative approach to criminal justice that focuses on victim recovery, offender rehabilitation and community reintegration. In the context of domestic and child violence, this approach offers the potential for more inclusive and sustainable solutions than traditional retributive approaches. However, there is debate about the effectiveness of RJ in cases of violence that have profound psychological and physical impacts on victims. The issue is whether RJ can provide adequate justice without compromising legal protections for victims. This research offers novelty by examining the application of RJ in cases of domestic and child violence in Indonesia and Fnland, where RJ laws and policies are still developing.